Envisioning Music Teacher Education - Wharton Conkling, Susan (Rowman & Littlefield Publishers, 2015)
This volume will contain selected proceedings from the 2013 Symposium on Music Teacher Education, sponsored by NAfME’s Society for Music Teacher Education and hosted at University of North Carolina. After an introduction written by SMTE Chair, Doug Orzolek, the initial chapter will represent the keynote address of the symposium by Karen Hammerness, Director of Program Research for the Bard Master of Arts in Teaching Program. Hammerness will bring her comparative work with music teacher educators in Finland and Norway to bear in her address: From Inspiring Visions to Everyday Practices: Exploring Vision and Practice in Music Teacher Education. Hammerness’s research distills into three main themes. To mitigate against the fragmentation that characterizes so much of contemporary education, teacher education programs must: 1) promote a clear vision of teachers and teaching; 2) be coherent, reflecting shared understanding of teaching and learning among faculty and students; 3) be built around a strong, core curriculum that is deeply tied to the practices of teaching. These three themes will orient the remainder of chapters in the volume, which will come from invited primary presenters at the 2013 Symposium. Due to selectivity of blind peer review (twenty-one percent accept rate), these presentations represent the most rigorous research, and best practices grounded in research, that the music education profession has to offer.